2019
DOI: 10.1371/journal.pone.0220319
|View full text |Cite
|
Sign up to set email alerts
|

A polyketide synthase gene cluster associated with the sexual reproductive cycle of the banana pathogen, Pseudocercospora fijiensis

Abstract: Disease spread of Pseudocercospora fijiensis , causal agent of the black Sigatoka disease of banana, depends on ascospores produced through the sexual reproductive cycle. We used phylogenetic analysis to identify P . fijiensis homologs (PKS8-4 and Hybrid8-3) to the PKS4 polyketide synthases (PKS) from Neurospora crassa and Sordaria macrospora involved in sexual reproduction. These sequences also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 85 publications
(125 reference statements)
0
15
0
Order By: Relevance
“…Both types of EVs were enriched with a polyketide synthase (X0LBU9) and a fusarubin cluster-esterase (X0KPE5), which may be involved in the production of pigments [45]. Polyketide synthases have been recognized as important machinery in the production of toxins from fungal pathogens of maize [46], banana [47], tobacco [48] and wheat [49], while the fusarubin cluster-esterase contributes to the production of the toxic pigment fusarubin, and has been detected in other pathogenic Fusarium species [50]. One enniatin synthase (X0KNM9) detected only in SDB EVs is involved in the production of enniatins and beauvericin, which are cyclic mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Both types of EVs were enriched with a polyketide synthase (X0LBU9) and a fusarubin cluster-esterase (X0KPE5), which may be involved in the production of pigments [45]. Polyketide synthases have been recognized as important machinery in the production of toxins from fungal pathogens of maize [46], banana [47], tobacco [48] and wheat [49], while the fusarubin cluster-esterase contributes to the production of the toxic pigment fusarubin, and has been detected in other pathogenic Fusarium species [50]. One enniatin synthase (X0KNM9) detected only in SDB EVs is involved in the production of enniatins and beauvericin, which are cyclic mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial data demonstrated that PKS-derived melanin is required for the development of asexual and sexual structures of fungi that might function as protectants against harmful environmental conditions. Deficiency of PKSs responsible for pigment biosynthesis usually had a negative effect on sexual development [19,[33][34][35]. Indeed, we previously demonstrated that downregulation of PKS-1/Alb1, a key enzyme responsible for pigment biosynthesis displayed a pigmentdeficient phenotype and lost the ability to produce ascospores in C. globosum [19].…”
Section: Discussionmentioning
confidence: 99%
“…fijiensis , given our interest in the polyketide toxin cercosporin in the related Cercospora species, as well as the importance of polyketides in pathogenicity by diverse fungi. In past work we identified one gene cluster ( PKS8-4 ) as being involved in spermagonia production during the sexual reproductive cycle [ 36 ]. Another PKS gene cluster ( PKS8-1 ) was shown to be conserved across three other Pseudocercospora species ( P .…”
Section: Discussionmentioning
confidence: 99%
“…Cercosporin is a perylenequinone produced through a polyketide synthase (PKS) pathway, thus previous work in the laboratory has focused on polyketide synthase gene clusters in P . fijiensis [ 34 36 ]. We conducted bioinformatics analyses that identified seven PKS genes ( PKS2-1 , PKS7-1 , PKS8-1 , PKS8-2 , PKS8-4 , PKS10-1 , and PKS10-2 ) and one hybrid PKS-nonribosomal peptide synthetase (NRPS) gene ( Hybrid8-3 ) in the P .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation